2020 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE) 2020
DOI: 10.23919/date48585.2020.9116230
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Qualifiable OpenMP Framework for Embedded Systems

Abstract: OpenMP is a very convenient programming model for critical real-time parallel applications due to its powerful tasking model and its proven time predictability. However, current implementations are not suitable for critical environments based on the intensive use of dynamically allocated memory needed to efficiently manage the parallel execution. This jeopardizes the qualification processes needed to ensure that the integrated software stack is compliant with system requirements. This paper proposes a novel Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…There are mainly two approaches for its adoption in high-integrity domains: 1. reusing the OpenMP specification and implementation for mainstream systems, i.e., as it is currently defined in its standard. However, this fails to cover many requirements for high-integrity systems [53,36].…”
Section: Multicore Programming Models (Openmp/pthreads/mtapi)mentioning
confidence: 99%
See 2 more Smart Citations
“…There are mainly two approaches for its adoption in high-integrity domains: 1. reusing the OpenMP specification and implementation for mainstream systems, i.e., as it is currently defined in its standard. However, this fails to cover many requirements for high-integrity systems [53,36].…”
Section: Multicore Programming Models (Openmp/pthreads/mtapi)mentioning
confidence: 99%
“…For use in high-integrity systems, runtimes need to be qualified according to the applicable functional safety standard and support documents. Recently, there have been some research proposals in this direction [53,36]. However, to our knowledge, the code of those solutions is neither publicly available nor qualified for use in the industry yet.…”
Section: Multicore Programming Models (Openmp/pthreads/mtapi)mentioning
confidence: 99%
See 1 more Smart Citation
“…This work strengthened the possibility of using OpenMP untied tasks (i.e., once such task is suspended by the initial thread, it can be correctly resumed by any idle thread within the same OpenMP team) on safety-critical embedded systems. A. Munera et al [10] showed how statically generated TDGs can reduce the dynamic memory usage of OpenMP tasks, so that the tasking model can be used on embedded systems conveniently, where the amount of dynamic memory is often limited by safety constraints. Taskgraph makes OpenMP more suitable for safety-critical embedded systems by reinforcing their work:…”
Section: Related Workmentioning
confidence: 99%
“…-Techniques used in [10] rely on the static generation of the TDG, the information from which can be leveraged by the taskgraph clause to enhance the performance. Therefore, by including the new clause in their method, the resulting framework should deliver better performance than the current OpenMP tasking model, and also use less dynamic memory throughout the execution.…”
Section: Related Workmentioning
confidence: 99%